Preliminary Phytochemical, Antioxidant and Antimicrobial Investigation of Selected Medicinal Plants of Khyber Pakhtunkhwa - Iftikhar Jan (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The majority of the people living in rural areas are still relying on traditional medicine for their primary healthcare needs. The locally available medicinal plants contain bioactive compounds that are widely used for the treatment of various chronic diseases caused by multidrug-resistant (MDR) microbes. However, research in this area has been limited. In this regard, the current study was designed on assessing the antimicrobial properties and phytochemical constituents of ethanol, methanol, hexane, ethyl acetate, and aqueous extracts of Ruellia tuberosa, Aesculus indica, and Myrsine africana against MDR microbes. The results of phytochemical analysis revealed the presence of different classes of secondary metabolites such as alkaloids, flavonoids, saponins, tannins, steroids, terpenoids, and reducing sugar, though anthraquinons, phlobatanins, and glycosides were absent in the selected plants. Furthermore, the quantitative analysis of methanol extract showed that M. africana had notable concentrations of total phenol (3.75 ± 0.05 mg 100g-1) and total flavonoid (11.39 ± 1.72 mg 100g-1) contents, while R. tuberosa had the highest (0.74 ± 0.06 mg 100g-1) tannins content. In addition, the lowest concentrations of total phenol (2.88 ± 0.04 mg 100g-1) and flavonoid (6.77 ± 1.02 mg 100g-1) were examined in A. indica, while the lowest tannin (0.31 ± 0.03 mg 100-1) moiety was observed in M. africana. Moreover, the mean highest (46.64%) antioxidant activity was observed for A. indica, while the lowest value was observed for M. africana (32.56%). The antimicrobial susceptibility test showed that ethanol, hexane, ethyl acetate, and aqueous extracts of the selected plants had remarkable inhibitory potential against the test bacterial and fungal species. The antimicrobial activity of selected plant extracts had no to low and moderate to good inhibitory potential against the test microorganisms.